Specialize early and select late: Performance trajectories of world-class finalists and international- and national-class swimmers - Born, D.-P.; Björklund, G.; Lorentzen, J.; Stöggl, T.; Romann, M. (International Journal of Sports Physiology and Performance, 2023)
Purpose To investigate performance progression from early-junior to peak performance age and compare variety in race distances and swimming strokes between swimmers of various performance levels.